2021
DOI: 10.1021/acsami.1c02611
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Antiswelling Loose Nanofiltration Membranes via a “Selective-Etching-Induced Reinforcing” Strategy for Bioseparation

Abstract: With diverse selectivity, higher permeance, and good antifouling property, loose polyamide nanofiltration (NF) membranes can be potentially deployed in various bioseparation applications. However, the loose NF membrane with a low crosslinking degree generally suffers from the alkali-induced pore swelling during chemical cleaning, resulting in degradation of separation performance with time. In this work, we conceive a novel strategy to tailor the separating layer through alkaline post-etching following the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…To further explore the membrane modification mechanisms, the effect of alkali etching pH on the membrane separation performance was evaluated. In previous study, we have confirmed that the higher etching pH could bring more hydrolysis of ester segments, which effectively enlarged the pores . In this work, we expect that the larger pore size can reduce the PEI diffusion resistance and deepen the PEI planting in the separation layer.…”
Section: Membrane Performancesupporting
confidence: 54%
See 1 more Smart Citation
“…To further explore the membrane modification mechanisms, the effect of alkali etching pH on the membrane separation performance was evaluated. In previous study, we have confirmed that the higher etching pH could bring more hydrolysis of ester segments, which effectively enlarged the pores . In this work, we expect that the larger pore size can reduce the PEI diffusion resistance and deepen the PEI planting in the separation layer.…”
Section: Membrane Performancesupporting
confidence: 54%
“…We further check the role of Fe 3+ in the membrane modification (Figure S6). Without the addition of Fe 3+ , the PEI-modified membrane shows overall low Na 2 SO 4 and glucose retentions (<30%), indicating that the chelation between Fe 3+ and TA can stabilize TA anchoring in the separation layer and facilitate the PEI grafting . Because the TA amount in the separation layer may govern the PEI grafting, the effect of PIP/TA ratio from 4:0 to 0:4 on the membrane performance was investigated.…”
Section: Membrane Performancementioning
confidence: 99%
“…Recently, a thin-film nanocomposite (TFN) membrane has been verified to raise filtration selectivity, via rational design and optimization of the structure and characteristics of the porous substrate and selective layer. , Numerous functional nanomaterials like zwitterionic, molybdenum disulfides, metal–organic frameworks (MOFs), and covalent-organic frameworks have been studied in the TFN membrane. Concrete manifestation in the reinforcement of polymer crosslinking degree, membrane hydrophilicity, and extra nanochannels facilitate water transportation. , By comparison, the amino-functionalized zirconium-based MOF (UiO-66-NH 2 ) is one of the most promising nanomaterials for efficient molecular separation, because of its high surface areas, ordered permanent porosity, superior chemical stability, and unique practical versatility. For example, the hydrophilic amino groups in UiO-66-NH 2 could be covalently bound in branched polyamide (PA) macromolecules, inhibiting the surface defect formation in the TFN membrane, and then exhibiting moderate rejection rates for Na 2 SO 4 (99.9%) and NaCl (38.1%) . Replacing partial Zr 4+ to Ti 3+ in UiO-66-NH 2 could neutralize some of the positive charges in the PA-TFN membrane, via a facile ion exchange method, which also achieved excellent mono-/divalent cation selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…17−20 Concrete manifestation in the reinforcement of polymer crosslinking degree, membrane hydrophilicity, and extra nanochannels facilitate water transportation. 15,21 By comparison, the amino-functionalized zirconium-based MOF (UiO-66-NH 2 ) is one of the most promising nanomaterials for efficient molecular separation, because of its high surface areas, ordered permanent porosity, superior chemical stability, and unique practical versatility. 22−25 For example, the hydrophilic amino groups in UiO-66-NH 2 could be covalently bound in branched polyamide (PA) macromolecules, inhibiting the surface defect formation in the TFN membrane, and then exhibiting moderate rejection rates for Na 2 SO 4 (99.9%) and NaCl (38.1%).…”
Section: Introductionmentioning
confidence: 99%
“…The production of thin freestanding, or reinforced polyelectrolyte layers is widely studied in literature [6,13,[22][23][24][25][26]. Reported manufacturing methods involve salt dilution induced phase separation [27,28], sacrificial layers [22,[29][30][31][32][33][34][35], deposition at liquid-liquid interfaces [13,36], deposition at gas-liquid interfaces [23,[37][38][39], and deposition by solvent evaporation [40,41].…”
Section: Introductionmentioning
confidence: 99%